PERCEPTION IN FORENSIC ACCOUNTING EDUCATION IN MALAYSIA: A COMPARISON BETWEEN ACCOUNTING UNDERGRADUATES AND PRACTITIONERS - Norzalina Mohamad Yusof; Dzarfan Abdul Kadir; Mohamad Naimi Mohamad Nor (Universitas Trisakti, 2007)
This study intends to gain insights on students' and practitioners' perception on demand for and interest in forensic accounting practices; relevance of forensic accounting education; important learning mechanisms; and topical content of forensic accounting education. A seven-part questionnaire was distributed to UUM students enrolled in Forensic Accounting course; and to practitioners, which include auditors and CFE members. The results reveal that both students and practitioners view highly on the benefits of forensic accounting education and expect to see an increase in future demand and interest in three areas of forensic accounting. However, practitioners feel that the present accounting curriculum is not sufficiently responsive to society's demand for forensic accounting education. Improvements in the curriculum content of forensic accounting subject are also needed. Topics such as cyber and computer fraud need to be given more attention in the classroom. The results of the study could be used by education providers in designing forensic accounting syllabus. JEL Classification : Keywords: Forensic Accounting, Accounting Education, Malaysia